Evaluation of radiation dose and image quality following changes to tube potential (kVp) in conventional paediatric chest radiography - Ramanaidu, S.; Sta Maria, R.B.; Ng, K.H.; George, John; Kumar, G. (Department of Biomedical Imaging, Faculty of Medicine, University of Malaya, 2006)
Purpose: A study of radiation dose and image quality following changes to the tube potential (kVp) in paediatric chest radiography. and Method: A total of 109 patients ranging from 1 month to 15 years were included in two phases of the study. Phase 1 investigated the range of entrance surface air kerma (ESAK) values received from patients exposed to the existing exposure factors. In the second phase, new exposure factors using recommended values of tube potential (kVp) with reduced mAs were used. ESAK values were measured using thermoluminescent dosemeters (TLDs). Image quality in both phases was evaluated using image quality criteria proposed by the Council of the European Communities (CEC). Results of both techniques were analysed for any differences. Results: The overall mean ESAK before the changes was 0.22 mGy (range: 0.05-0.43) Following changes in tube potential, the overall mean reduced to 0.15 mGy (range: 0.03-0.38), a significant reduction by 34%. The interquartile range was reduced from 45% to 40%. However, doses to those below a year in age still remained high. Assessment of image quality was found to have no significant differences as far as the two techniques used were concerned. However, higher image scores were achieved using higher kVps. Conclusion: Significant dose reduction was achieved through appropriate changes in tube potential and reduction of mAs without any loss in image quality. © 2006 Biomedical Imaging and Intervention Journal. All rights reserved